Information Security Breaches : Avoidance and Treatment based on ISO27001. - Krausz, Michael (IT Governance Pub., 2009)
This pocket guide outlines a process and its elements for the treatment of severe breaches, and places them in the context of the associated ISO27001 controls. Firslty it offers a general discussion of what information security breaches are, and secondly it helps rform a first line of defence for the reader who is the victim of an incident and is looking for guidance and direction.